Tree host–pathogen interactions as influenced by drought timing: linking physiological performance, biochemical defence and disease severity. (9th October 2018) - Hossain, Mohitul; Veneklaas, Erik J; Hardy, Giles E St J; Poot, Pieter
Abstract: There is increasing concern about tree mortality around the world due to climatic extremes and associated shifts in pest and pathogen dynamics. Yet, empirical studies addressing the interactive effect of biotic and abiotic stress on plants are very rare. Therefore, in this study, we examined the interaction between drought stress and a canker pathogen, Quambalaria coyrecup, on the eucalypt – Corymbia calophylla (marri), which is experiencing increasing drought stress. We hypothesized that drought stress would increase marri's susceptibility to canker disease, and cankers would have the largest negative effect on plants that are already drought stressed before pathogen inoculation. To test the hypotheses, in a glasshouse, marri saplings were exposed to drought either before or after pathogen inoculation, or were well-watered or droughted throughout the experiment either with or without inoculation. Canker development was greater in well-watered saplings than in droughted saplings, with the fastest development occurring in well-watered saplings that had experienced drought stress before inoculation. Irrespective of water treatments, marri saplings employed phenol-based localized biochemical defence against the pathogen. Drought reduced photosynthesis and growth, however, a negative effect of canker disease on saplings' physiological performance was only observed in well-watered saplings. In well-watered saplings, canker-induced loss of sapwood function contributed to reduced whole-plant hydraulic conductance, photosynthesis and growth. The results provide evidence that timing of drought stress influences host physiology, and host condition influences canker disease susceptibility through differences in induced biochemical defence mechanisms. The observations highlight the importance of explicitly incorporating abiotic and biotic stress, as well as their interactions, in future studies of tree mortality in drought-prone regions worldwide.